Exploring the Use of Artificial Intelligence in Developing Writing Skills: A Systematic Review - Salem Shibani (AlQalam Journal of Medical and Applied Sciences, 2025)
This systematic review aims to evaluate the capabilities of AI over the last decade in generating ideas, critiquing essays, crafting stories, and providing writing feedback, particularly for writing scholars. The study seeks to help educators, researchers, and application developers understand the potential of AI in writing by addressing existing gaps in the literature. The findings indicate that AI is progressing in its role within the educational framework, highlighting new opportunities for developing writing assistance tools. In summary, integrating AI into writing instruction offers benefits for both students and teachers. For educators, AI tools present a way to enhance their teaching methods while preserving essential educational values. For students, AI serves as a valuable resource for their creative endeavors. With thoughtful integration, AI can complement traditional teaching, fostering an educational environment where technology enhances the human elements of learning and writing, rather than detracting from them. Future studies should also explore the social, emotional, and psychological impacts of AI writing tools on students. Understanding how these tools shape students’ perceptions of writing, motivation, and self-efficacy is crucial as interactions with AI technologies increase. Research could be conducted to determine whether the use of AI tools boosts students’ confidence in their writing skills or diminishes it by comparing human work with that of AI systems. In this context, students’ expressions of their emotional experiences will provide valuable insights into the different ways they engage with AI support in writing.